Haemophilus influenzae Pyomyositis in a Patient with Diabetic Ketoacidosis: A Unique Case and Review of Literature - Kamolyut Lapumnuaypol; Sanna Fatima; Pradhum Ram; Gemlyn George; Antoinette Climaco (Case Reports in Infectious Diseases)
Haemophilus influenzae is a Gram-negative bacillus commonly known to cause upper respiratory tract infections. Skin and soft tissue infections are very uncommon. Of these, the majority were associated with necrotizing fasciitis requiring emergent debridement. We report a case of pyomyositis caused by Haemophilus influenzae in an adult with diabetes.